Proteomics: Potential techniques for discovering the pathogenesis of connective tissue diseases-interstitial lung disease - Wu, Yinlan; Li, Yanhong; Luo, Yubin; Zhou, Yu; Liang, Xiuping; Cheng, Lu; Wu, Tong; Wen, Ji; Tan, Chunyu; Liu, Yi (Frontiers in Immunology, 2023)
Interstitial lung disease (ILD) is one of the most serious lung complications of connective tissue disease (CTD). In the past decade, the application of proteomics has revealed that a variety of proteins are involved in the pathogenesis of each subtype of CTD-ILD through different pathways, which provides new ideas for the study of pathological mechanisms and clinical biomarkers. On this basis, a multidimensional diagnosis or prediction model is established. This paper reviews the results of proteomic detection of different subtypes of CTD-ILD, and discusses the role of some differentially expressed proteins in the development of pulmonary fibrosis and their potential clinical applications.